Health Care Financing and Affordability in the Emerging Global Markets - Kyriakos Souliotis (Frontiers Research Topics, 2016)
During the recent few decades, global economic growth has been driven largely by developing world economies. The ones with the most intensive pace of development were marked as "emerging" markets led by so called BRICS and N-11 countries. Such changes inevitably reflected the global health arena. A number of issues previously limited to established high-income economies became popularly discussed topics on the agendas of public health policy makers across these regions. Major challenges remain population aging, rising incidence of prosperity diseases, lack of universal insurance coverage and particularly provision of just and equitable access to medical care among the poor both in urban and rural communities. A significant part of the difficulties faced by these societies are attributed to inefficient resource allocation strategies in health care and unsatisfactory funding strategies. This Research Topic was created in order to address the core challenges of medical care financing and its affordability across the emerging global markets. Contributions of both undergoing or finished original research as well as review style papers are welcomed. All submitted manuscripts should deal with issues relevant to health care economics and policy in recognized global emerging markets. Outside the aforementioned key markets (BRICS- Brazil, Russia, India, China, South Africa; Next 11- Bangladesh, Egypt, Indonesia, Iran, South Korea, Mexico, Nigeria, Pakistan, the Philippines, Turkey and Vietnam) submissions referring to any of the dynamically developing Asian, Latin America, Eastern Europe or MENA countries are encouraged. In addition to a variety of health-economic evaluations and health policy analysis, methodological and resource use studies are within the Topic scope. Health policy considerations should be primarily focused on financing mechanisms and affordability of health care although other surrounding issues such as health insurance, reimbursement and cost-containment strategies will be considered.